Gravity anomalies of the Southeast Caucasus - G.R. Sadygova (Геофизический журнал, 2020)
The article studies gravity anomalies of disturbing masses by the values of the power spectrum and digital filtering of gravity data. The calculation of the power spectrum and digital filtering is performed using the Hartley transform and Butterworth filter. Processing of gravimetric data in the frequency component makes it possible to estimate the depths of anomaly-forming sources by analysing the radial spectrum. The logarithm of the power spectrum is graphically described depending on the spatial frequency, to determine the depth of density boundaries. The low-frequency and high-frequency components and the cutoff frequency are determined from the curve of the logarithm of the power spectrum. The cutoff frequency separating the regional and local components is determined by the point of intersection of the lines obtained by approximating the data of the power spectrum in the long and short wavelength components. The cutoff frequency (wavenumber) is determined to be equal to ωc = 0.16 rad/km in this case. Low-frequency and high-frequency components are accepted as components of regional and local anomalies. The power spectrum indicates depths of 16.6 km for the long component and 1.8 km for the short components. The depth of 16.6 km is connected with the surface of the crystalline basement, and 1.8 km with the surface inside the Cenozoic sediments. Good agreement between the results of filtering gravimetric data of the Southeast Caucasus using the Hartley transform and the one-dimensional Butterworth filter with the results of previous studies confirm the reliability of the results.The interpretation of the regional anomalies shows that these anomalies depend on geometry crystalline basement.